Thrombin Induces Thromboplastin Synthesis in Cultured Vascular Endothelial Cells - Galdal, K S; Lyberg, T; Evensen, S A; Nilsen, E; Prydz, H (Thrombosis and Haemostasis, 1985)
Cultured human umbilical vein endothelial cells responded to thrombin (10−2 – 10 NIH u/ml) with a 2-5 fold increase in thromboplastin activity. The maximum response was reached after 4 hr in serum-free medium. The effect of thrombin was fully inhibited by the presence of 50% (v/v) fetal calf serum or more in the medium, by preincubation of thrombin with hirudin or by treatment of thrombin with N-bromosuccinimide or phenylmethylsulfonyl fluoride. The thrombin-induced thromboplastin activity was inhibited by incubation of the cells with cycloheximide (2 μg/ml) or actinomycin D (2 μg/ml) showing that the response depended on de novo protein and RNA synthesis. It was also suppressed by exposure of the cells to two different phosphodiesterase inhibitors, 3-butyl-l-methyl-xanthine (5 · 10−4 M) and rac-4 (3-butoxy-4-methoxybenzyl)-2-imidazole (5 · 10−4 M), to the transmethylation inhibitors 3-deazaadenosine (10−5 M) and 1-homocysteine thiolactone (2 · 10−5 M) in combination and to the intracellular calcium antagonist 8-(N,N-diethylamino)-octyl 3,4,5,-tri-methoxybenzoate hydrochloride (8 · 10−5 M). Our results suggest that small amounts of thrombin can induce thromboplastin synthesis in endothelial cells in vitro and that this synthesis probably is regulated by the intracellular level of cAMP, by cytoplasmic Ca2+ and possibly also by transmethylation reactions.
Keywords: Endothelial cells; Thrombin; Thromboplastin